1976
DOI: 10.1111/j.1365-2621.1976.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

The assay of conjugable oxidation products applied to lipid deterioration in stored foods

Abstract: A new analytical procedure, determining oxidation products of polyenoic fatty acids, is applied to both fresh and stored foods and fats. The extent of deterioration of the extracted lipid is measured by changes in the ultraviolet spectrum resulting from the chemical reaction steps of the assay-the results are compared with the traditional peroxide value. In the assay not only hydroperoxides of polyenoic fatty acids but also hydroxy and carbonyl compounds derived from them, yield 'conjugable oxidation products'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 4 publications
1
13
0
2
Order By: Relevance
“…At intervals during the storage period samples were homogenized and extracted with chloroform-methanol (Bligh and Dyer, 1959) and aliquots of the chloroform taken for the different analyses. Because of difficulties in obtaining reproducible TBA values, oxidative changes in fatty acids were estimated by the method of Parr and Swoboda (1976;also Fishwick and Swoboda, 1977;Streiff et al, 1977). This technique invokes the following spectrometric measurements: 1) oxodiene value (OV), which represents diene conjugation after reduction of the keto groups of oxodiene fatty acids, to hydroxy groups; 2) conjugable oxidation products (COP) obtained by dehydration of fatty acids hydroperoxides, oxodienes, and hydroxydienes; and 3) the conjugated oxidation products ratio (COPR), which is a measure of the relative amounts of conjugated tri-and tetraenes formed in the dehydration mixture.…”
Section: Male Turkey Poults (Meleagris Gallopavo)mentioning
confidence: 99%
“…At intervals during the storage period samples were homogenized and extracted with chloroform-methanol (Bligh and Dyer, 1959) and aliquots of the chloroform taken for the different analyses. Because of difficulties in obtaining reproducible TBA values, oxidative changes in fatty acids were estimated by the method of Parr and Swoboda (1976;also Fishwick and Swoboda, 1977;Streiff et al, 1977). This technique invokes the following spectrometric measurements: 1) oxodiene value (OV), which represents diene conjugation after reduction of the keto groups of oxodiene fatty acids, to hydroxy groups; 2) conjugable oxidation products (COP) obtained by dehydration of fatty acids hydroperoxides, oxodienes, and hydroxydienes; and 3) the conjugated oxidation products ratio (COPR), which is a measure of the relative amounts of conjugated tri-and tetraenes formed in the dehydration mixture.…”
Section: Male Turkey Poults (Meleagris Gallopavo)mentioning
confidence: 99%
“…To quantitate the effects of extrusion temperature on the extruded corn meal samples, the oil was extracted with petroleum ether after storage for selected intervals. The solvent was removed under a stream of nitrogen and the peroxide values (AOAC, 1984), the conjugable oxidation product values (COP), plus the oxodiene values were determined (Parr and Swoboda, 1976). The COP value is the sum of the absorbance increases at 268 and 301 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The isomers were identified as a-eleostearic acid (9c,11t,13t-18:3), b-eleostearic acid (9t,11t,13t-18:3), and 8t,10t,12t-18:3. The possible mechanism for formation of these CLN isomers involves linoleate oxidation, reduction of hydroperoxide to the hydroxide, and dehydration [16,17]. We also found that 8,10,12 and 9,11,13-CLN were formed during bleaching of soybean oil [18].…”
Section: Introductionmentioning
confidence: 79%